Environmental Management System and Financial Performance of Environmentally Sensitive Industries in South Africa - Thomas NYAHUNA; Mishelle DOORASAMY (Indonesia Strategic Sustainability, 2023)
The influence of environmental management system (EMS) on corporate financial performance within the African corporate context has persistently remained lacking and inconclusive, attributed primarily to the absence of data. However, this study investigates the influence of EMS on corporate financial performance measured by earnings per share (EPS) of 65 Johannesburg Stock Exchange listed environmental sensitive companies from 2014 to 2018. Size was used as a control variable. Using SPPS version 28, this study discover vast evidence of a favourable association between EMS and EPS. The importance of EMA cannot be underestimated. Therefore, this study makes available valuable insights on in what way companies can wholly apply EMS to upsurge corporate financial performance. It was concluded that the government should regulate the implementation of EMS within companies as a source of climate change mitigation and as a strategy to upswing financial and environmental performance.